The Wilderness Campaign - Gallagher, Gary W. (Book collections on Project MUSE., 1997)
In the spring of 1864, in the vast Virginia scrub forest known as the Wilderness, Ulysses S. Grant and Robert E. Lee first met in battle. The Wilderness campaign of May 5-6 initiated an epic confrontation between these two Civil War commanders - one that would finally end, eleven months later, with Lee's surrender at Appomattox. The eight essays here assembled explore aspects of the background, conduct, and repercussions of the fighting in the Wilderness.